Cyberbullying di Era Digital dan Implikasinya terhadap Perilaku Mad’u: Analisis Psikologi Dakwah Berbasis Hierarki Kebutuhan Maslow - Iwan Supriyanto; M. Adkha Rosadi; Supatmi; Meity Suryandari (Journal of Education and Learning Sciences, 2026)
The rapid development of digital technology has intensified social interactions through social media, but it has also led to the emergence of cyberbullying, which affects the psychological condition and behavior of mad’u. This study addresses how cyberbullying influences mad’u behavior and how it can be analyzed using Maslow’s Hierarchy of Needs within the framework of da’wah psychology. This research employs a qualitative approach using library research by analyzing relevant scholarly literature. The findings reveal that cyberbullying is closely related to the imbalance in fulfilling psychological needs, including safety, belongingness, esteem, and self-actualization. This condition contributes to the emergence of aggressive behavior and unethical digital communication. The study concludes that a da’wah psychology approach based on Maslow’s theory can serve as an effective strategy in shaping more ethical, empathetic, and spiritually grounded mad’u behavior in the digital era.